The Angiotensin II Type 2 Receptor in Brain Functions: An Update - Marie-Odile Guimond; Nicole Gallo-Payet (International Journal of Hypertension)
Angiotensin II (Ang II) is the main active product of the renin-angiotensin system (RAS), mediating its action via two major receptors, namely, the Ang II type 1 (AT1) receptor and the type 2 (AT2) receptor. Recent results also implicate several other members of the renin-angiotensin system in various aspects of brain functions. The first aim of this paper is to summarize the current state of knowledge regarding the properties and signaling of the AT2 receptor, its expression in the brain, and its well-established effects. Secondly, we will highlight the potential role of the AT2 receptor in cognitive function, neurological disorders and in the regulation of appetite and the possible link with development of metabolic disorders. The potential utility of novel nonpeptide selective AT2 receptor ligands in clarifying potential roles of this receptor in physiology will also be discussed. If confirmed, these new pharmacological tools should help to improve impaired cognitive performance, not only through its action on brain microcirculation and inflammation, but also through more specific effects on neurons. However, the overall physiological relevance of the AT2 receptor in the brain must also consider the Ang IV/AT4 receptor.